Net zero business models : winning in the global net zero economy - Montgomery, John B.; Van Clieaf, Mark (Wiley, 2023)
"Climate change is not only a carbon-centric issue but, at its core, a business model design, business strategy, and long horizon risk management issue. However, the prevailing conversation has grossly underestimated the enormity of the issue and the scale of change and transformation required with both listed public companies and private companies as well. For example, in collaboration with Credit Suisse Holt ℗ʼ, Mark's consultancy, FutureZero, undetook a carbon-shock stress test to over 11,100 global securities. They found that companies with over $20 trillion of enterprise value are at material risk of suffering a significant loss of value because their current business models are not viable in the face of such a carbon shock. In other words, the prevailing conversation has greatly underestimated the systemic risk to the financial markets caused by the need to conform business models to a net zero emissions economy. As a result, most companies are unprepared for the transition. Approximately 32% have increased their greenhouse gas (GHG) emissions over the last 8 years; 25% have had small GHG reduction; and in North America 63% of companies are not aligned with the Paris COP21/26 goals for the world. The world is heading the wrong way, and we need a rocket booster to have the transformation go mainstream."--